Analytical characteristics of olive oils produced by two different extraction techniques in the portuguese olive variety Galega Vulgar - Vaz-Freire, Luís (2008)
A metal hammer-decanter (HD) olive processing line was compared to a traditional metal hammer-press (HP) line, a discontinuous method which, when properly used, yields high-quality virgin olive oils. Galega olives (traditional Portuguese variety) were used. Olives were picked at a predetermined maturation stage and plagues and oil content were evaluated before processing. Years, extraction technology, data replicates, and years*extraction, were taken into account and compared using statistical treatment. In spite of significant differences among the results obtained, only acidity was statistically significant and sufficient for classifying the produced olive oil into a lampante category